The effect of jugular foramen volume on the development of idiopathic intracranial hypertension - Ertugrul, Bilal; Simsek, Hakan; Komurcu, Harun; Baykara, Murat; Kaplan, Metin (Sage Publications Ltd, 2026)
Introduction Idiopathic intracranial hypertension is a condition characterized by elevated intracranial pressure in the absence of an intracranial mass lesion and is commonly associated with neuro-ophthalmic symptoms. Although venous outflow abnormalities, particularly transverse sinus stenosis, have been extensively investigated in idiopathic intracranial hypertension, the potential role of jugular foramen volume has not been previously studied. Considering that major venous structures pass through the jugular foramen, this study aimed to evaluate whether jugular foramen volume plays a role in the development of idiopathic intracranial hypertension.Methods Forty patients who were diagnosed and followed up for idiopathic intracranial hypertension according to the modified Friedman criteria were included in the study. A control group of 40 individuals without idiopathic intracranial hypertension was randomly selected from the same archive. Jugular foramen volumes were measured using cranial computed tomography scans retrieved from the institutional archive. Age, sex, and bilateral jugular foramen volumes were recorded.Results No statistically significant differences were found between the idiopathic intracranial hypertension and control groups regarding right, left, or total jugular foramen volumes. The mean right jugular foramen volume was 1.574 +/- 0.407 cm & sup3; in the idiopathic intracranial hypertension group and 1.538 +/- 0.308 cm & sup3; in the control group; the mean left jugular foramen volumes were 1.474 +/- 0.316 cm & sup3; and 1.471 +/- 0.246 cm & sup3;, respectively. No significant association was observed between jugular foramen volume and the development of idiopathic intracranial hypertension (p = 0.7438).Conclusion Jugular foramen volume does not appear to contribute to the development of idiopathic intracranial hypertension. This finding suggests that venous abnormalities associated with idiopathic intracranial hypertension are functional rather than related to static bony anatomy. Further studies with larger cohorts and detailed compartment-based anatomical assessments are warranted.
Keywords: Idiopathic intracranial hypertension; jugular foramen; intracranial pressure; venous outflow; cranial computed tomography volumetry